Parameters of hepatotoxic reactions caused by the combination of first line anti-tuberculosis drugs in rats with different acetylation phenotypes - G. N. Mozhokina; А. V. Kazakov; Yu. R. Zyuzya; L. Yu. Petrova (Туберкулез и болезни лёгких)
The objective: in the experiment, to study specific parameters of manifestations of hepatotoxic reactions to the combination of anti-tuberculosis drugs containing isoniazid and rifampicin in rats with different acetylation phenotypes. Subjects and methods. Liver damage was modeled in rats, old females, belonging to the phenotype of rapid acetylation, and in mature males, belonging to the phenotype of slow acetylation, with a combination of basic anti-tuberculosis drugs, which were administered for 14 days. Hepatotoxic reactions were assessed by clinical observations of rats, biochemical parameters and morphological changes in the liver, which were compared with intact animals. Results of the study: in female rats (fast acetylators of isoniazid), signs of the cytolytic mechanism of liver damage prevailed (more significant elevation of ALT activity, pronounced duration of thiopental sleep, pronounced hydropic degeneration of hepatocytes with the presence of hepatocyte necrosis, venous congestion and edema of the portal tracts). In males (with the phenotype of slow acetylation of isoniazid), a significant elevation of total and direct bilirubin levels, AST activity and, to a lesser extent, ALT were observed, i.e., signs of a mixed mechanism of liver damage (cholestatic and cytolytic).